The Coexistence of Gravity Waves From Diverse Sources During a SOUTHTRAC Flight. Issue 5 (25th February 2023) - Alexander, P.; de la Torre, A.; Llamedo, P.; Hierro, R.; Marcos, T.; Kaifler, B.; Kaifler, N.; Geldenhuys, M.; Preusse, P.; Giez, A.; Rapp, M.; Hormaechea, J. L.
Abstract: We use observations from one of the SOUTHTRAC (Southern Hemisphere Transport, Dynamics, and Chemistry) Campaign flights in Patagonia and the Antarctic Peninsula during September 2019 to analyze possible sources of gravity waves (GW) in this hotspot during austral late winter and early spring. Data from two of the instruments onboard the German High Altitude and Long Range Research Aircraft (HALO) are employed: the Airborne Lidar for Middle Atmosphere research (ALIMA) and the Basic HALO Measurement and Sensor System (BAHAMAS). The former provides vertical temperature profiles along the trajectory, while the latter gives the three components of velocity, pressure, and temperature at the flight position. GW‐induced perturbations are obtained from these observations. We include numerical simulations from the Weather Research and Forecast (WRF) model to place a four‐dimensional context for the GW observed during the flight and to present possible interpretations of the measurements, for example, the orientation or eventual propagation sense of the waves may not be inferred using only data obtained onboard. We first evaluate agreements and discrepancies between the model outcomes and the observations. This allowed us an assessment of the WRF performance in the generation, propagation, and eventual dissipation of diverse types of GW through the troposphere, stratosphere, and lower mesosphere. We then analyze the coexistence and interplay of mountain waves (MW) and non‐orographic (NO) GW. The MW dominate above topographic areas and in the direction of the so‐called GW belt, whereas the latter waves are mainly relevant above oceanic zones. WRF simulates NOGW as mainly upward propagating entities above the lower stratosphere. Model runs show that deep vertical propagation conditions are in general favorable during this flight but also that in the upper stratosphere and lower mesosphere and mainly above topography there is some potential for wave breaking. The numerical simulations evaluate the GW drag for the whole flight area and find that the strongest effect is located in the zonal component around the stratopause. The general behavior against height resembles that obtained with a local fixed lidar data. According to WRF results, up to 100 km horizontal wavelength MW account for about half of the force opposing the circulation of the atmosphere. Plain Language Summary: We use observations from one of the SOUTHTRAC (Southern Hemisphere Transport, Dynamics, and Chemistry) Campaign flights in Patagonia and the Antarctic Peninsula during September 2019 to analyze possible sources of atmospheric waves. Data from two of the cutting‐edge instruments onboard the German High Altitude and Long Range Research Aircraft (HALO) are employed. They provide velocity, pressure, and temperature at the flight position and above. We include numerical simulations to place a four‐dimensional context for the waves observed during the flight. Agreements and discrepancies between the model outcomes and the observations are evaluated. We then analyze the coexistence of waves generated by the mountains and other sources. Key Points: There is evidence for the simultaneous and collocated presence of mountain waves and non‐orographic gravity waves during a SOUTHTRAC flight MW dominated above sharp topography in Southern Patagonia and southeastwards. NOGW predominated above the oceans WRF simulations up to the mesosphere against onboard‐based observations show good GW representation in temperature perturbations and fair in vertical velocity